Magnetic powder with super-hydrophobic surface and preparation method and application thereof
Patent Information
- Application Number
- CN202211645211.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-21
AI Technical Summary
[0005]本发明的目的在于解决稀土磁粉不耐水特别是在热水中耐水性较差的问题,提出了一种具有超疏水表面的磁粉及其制备方法和应用,制备过程简单、成本低,疏水层厚度均匀、可控,有效提高了磁粉的耐水性
[0024](1)本发明采用苯并咪唑类物质和有机酸联用,促使在磁粉表面形成相互交织、均匀致密的疏水层,显著提升磁粉的耐水性,在热水中浸泡后也能保持较高的磁性能。
Smart Images

Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnetic materials technology, specifically relating to a magnetic powder with a superhydrophobic surface, its preparation method, and its application. Background Technology
[0002] Plastic magnetic materials are obtained by mixing and granulating magnetic materials and polymer materials at 200-350℃, followed by injection extrusion or molding. Using thermoplastic resins such as nylon (e.g., PA12), polyphenylene sulfide, and elastic plastics as the matrix, they are mixed with magnetic powders such as ferrite, samarium iron nitrogen, neodymium iron boron, and samarium cobalt. Injection molding technology has a unique advantage in the integral molding of thin-walled, complex-shaped magnetic materials, and the resulting magnetic materials have high dimensional accuracy and good mechanical properties, playing a key role in promoting the miniaturization, lightweighting, efficiency, and energy saving of magnetic devices.
[0003] As an indispensable part of an electric motor, the rotor, manufactured by injection molding, can significantly reduce material costs. Furthermore, the rotor boasts high dimensional accuracy, high mechanical strength, and a large design flexibility. Rotors made from rare-earth magnetic powders such as NdFeB, SMA, and SMA are prone to corrosion in air due to reactions with water and oxygen. Rotors used in water pumps operate in even harsher environments, requiring resistance to both high temperatures and water. Therefore, the stability requirements for the magnets are even more stringent. Plastic magnetic components are generally directly molded without further surface treatment, which places higher demands on the water resistance and oxidation resistance of the magnetic powder itself.
[0004] Rare earth magnetic powders are highly reactive due to the high activity of rare earth elements, making them prone to corrosion and oxidation upon contact with water and air, leading to a loss of coercivity in the magnets. This is especially true for magnetic powders used in injection-molded magnets, where the average particle size is typically less than 100 μm, and the surface of these fine powders is extremely susceptible to corrosion. Water resistance and oxidation resistance can generally be improved by element doping or surface coating. However, element doping alters the composition of the magnetic powder, resulting in a decrease in its performance. Coating the magnetic powder surface with a stable metal element using methods such as ion sputtering is costly and not feasible for large-scale production. Summary of the Invention
[0005] The purpose of this invention is to solve the problem of poor water resistance of rare earth magnetic powder, especially in hot water. It proposes a magnetic powder with a superhydrophobic surface, its preparation method and application. The preparation process is simple and low-cost, and the thickness of the hydrophobic layer is uniform and controllable, which effectively improves the water resistance of the magnetic powder.
[0006] The technical solution adopted by this invention to achieve its objective is as follows:
[0007] Firstly, this invention proposes a method for preparing magnetic powder with a superhydrophobic surface. Benzimidazole-based substances are used as the main material for forming the hydrophobic layer. After the surface treatment solution is prepared, it is mixed with the magnetic powder. During the interaction process, imidazole molecules adsorb onto the magnetic powder surface by forming coordination bonds with the metal. Non-polar groups also form a hydrophobic protective film on the magnetic powder surface. Specifically, the method includes the following steps:
[0008] Step (1): Add a certain mass of benzimidazole and salts containing transition metal ions to an organic solvent to obtain solution A;
[0009] Step (2): Add organic acid to solution A and adjust the pH value of the solution to 5.5-6.5. Stir to disperse the solution evenly to obtain solution B;
[0010] Step (3): Add a certain amount of magnetic powder to solution B in step (2), stir ultrasonically, transfer to a vacuum oven, and dry to obtain magnetic powder with a superhydrophobic surface.
[0011] Preferably, the benzimidazole substance mentioned in step (1) is used as a film-forming agent, and one or more of alkylbenzimidazole and phenylbenzimidazole are used, more preferably 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole.
[0012] Preferably, the mass ratio of the benzimidazole substance to the magnetic powder in step (1) is 0.1%-0.5%:100%, and the thickness of the hydrophobic layer is between 100-300 nm.
[0013] Preferably, the transition metal ions in the salt containing transition metal ions in step (1) are one or more of copper ions, iron ions, and zinc ions, with iron ions being more preferred.
[0014] Preferably, the salt containing transition metal ions in step (1) is a chloride salt.
[0015] Preferably, the mass ratio of the transition metal ion-containing salt to the benzimidazole substance in step (1) is 10%:100%.
[0016] Preferably, the organic acid mentioned in step (2) is one or more of ascorbic acid and tartaric acid, and more preferably ascorbic acid.
[0017] Preferably, the magnetic powder mentioned in step (3) is one or more of neodymium iron boron, samarium iron nitrogen, and samarium cobalt.
[0018] Preferably, in step (3), the magnetic powder and solution B are mechanically stirred in a water bath at 40°C until the reaction is complete, and then dried in a vacuum oven at 60°C.
[0019] Secondly, this invention proposes a magnetic powder with a superhydrophobic surface.
[0020] Thirdly, a permanent magnet is obtained by mixing magnetic powder with a resin matrix and then injection molding.
[0021] Preferably, the mass ratio of magnetic powder to resin matrix is 9:1.
[0022] Preferably, the resin matrix is PA12 resin.
[0023] The beneficial effects of this invention are as follows:
[0024] (1) The present invention uses benzimidazole substances and organic acids in combination to promote the formation of an interwoven, uniform and dense hydrophobic layer on the surface of magnetic powder, which significantly improves the water resistance of magnetic powder and can maintain high magnetic properties even after being soaked in hot water.
[0025] (2) The experimental steps of the method of the present invention are simple, the parameters are controllable, and no precision equipment is required. Existing basic equipment can meet the processing requirements.
[0026] (3) The present invention can form a dense hydrophobic layer with a small amount of imidazole, and the magnetic properties of the magnetic powder will not decrease due to excessive addition.
[0027] (4) The main component of the hydrophobic layer of the present invention is organic matter, which can be directly mixed with resin and other binders to prepare composite plastic magnets without further surface treatment, eliminating the conventional coupling surface modification process and simplifying the process.
[0028] (5) The hydrophobic layer of the present invention is not only water resistant but also high temperature resistant. The decomposition temperature of 300°C or above can fully meet the temperature requirements when magnetic powder and resin materials are mixed, which is beneficial for the preparation of high-performance products. Detailed Implementation
[0029] As mentioned above, in view of the shortcomings of the prior art, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention, the main basis of which includes at least the following:
[0030] Benzimidazoles can form a hydrophobic layer on the surface of magnetic powder. When magnetic powder for injection molding is mixed and granulated with polymer materials at a temperature between 200-350℃, the hydrophobic layer is required to have the ability to withstand high-temperature decomposition. The introduction of phenyl groups can increase the decomposition temperature of benzimidazoles, with phenylbenzimidazole having the best decomposition temperature above 350℃.
[0031] The preferred benzimidazole material in this invention is 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole, which has a good adsorption effect on iron due to its nitrogen-containing organic composition; the 14 carbon atoms ensure that it has sufficient molecular volume to form a tight hydrophobic layer on the magnetic powder surface, while avoiding the increase in molecular motion resistance due to excessively long hydrocarbon groups, which would affect the coating effect; and the dichlorophenyl molecule structure introduces chloride ions, which can generate specific adsorption, as a coordinating component.
[0032] The benzimidazole-based substance comprises 0.1%-0.5% of the magnetic powder by mass, forming a hydrophobic layer with a thickness between 100-300 nm. If the addition amount is less than 0.1%, the hydrophobic layer is too thin and incomplete, which is not conducive to the long-term effective protection of the magnetic powder; if the addition amount is greater than 0.5%, the coating layer is too thick, which leads to a decrease in the remanence of the magnetic powder. Considering that water in the solvent will have an adverse effect on the magnetic powder, the organic solvent is selected from commonly used organic solvents such as ethanol, isopropanol, and acetone with a purity greater than 95%.
[0033] The addition of transition metal ions such as copper, zinc, and iron ions in this invention can promote the formation of a hydrophobic layer. For iron-based magnetic powders, the addition of iron ions yields the best results.
[0034] The addition of organic acids in this invention serves two purposes. First, lowering the pH of the solution increases the solubility of imidazole in organic solvents, promoting the formation of a hydrophobic layer on the magnetic powder surface. Second, the surface of magnetic powder is complex, and the hydrophobic layer formed by imidazole may be uneven and not dense during the formation process. Adding acidic substances that can also form films on the magnetic powder surface, in synergy with imidazole, forms a more uniform and dense protective film with better water resistance than a single component.
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0036] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0037] A method for preparing magnetic powder with a superhydrophobic surface uses benzimidazole-based substances as the main material for forming the hydrophobic layer. After the surface treatment solution is prepared, it is mixed with the magnetic powder. During the interaction process, imidazole molecules adsorb onto the magnetic powder surface by forming coordination bonds with the metal. Non-polar groups also form a hydrophobic protective film on the magnetic powder surface. Specifically:
[0038] Step (1): Add a certain mass of benzimidazole and salts containing transition metal ions to an organic solvent to obtain solution A;
[0039] Step (2): Add organic acid to solution A and adjust the pH value of the solution to 5.5-6.5. Stir to disperse the solution evenly to obtain solution B;
[0040] Step (3): Add a certain amount of magnetic powder to solution B in step (2), stir ultrasonically, transfer to a vacuum oven, and dry to obtain magnetic powder with a superhydrophobic surface.
[0041] Preferably, the benzimidazole substance mentioned in step (1) is used as a film-forming agent, and one or more of alkylbenzimidazole and phenylbenzimidazole are used, more preferably 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole.
[0042] Preferably, the mass ratio of the benzimidazole substance to the magnetic powder in step (1) is 0.1%-0.5%:100%, and the thickness of the hydrophobic layer is between 100-300 nm.
[0043] Preferably, the transition metal ions in the salt containing transition metal ions in step (1) are one or more of copper ions, iron ions, and zinc ions, with iron ions being more preferred.
[0044] Preferably, the salt containing transition metal ions in step (1) is a chloride salt.
[0045] Preferably, the mass ratio of the transition metal ion-containing salt to the benzimidazole substance in step (1) is 10%:100%.
[0046] Preferably, the organic acid mentioned in step (2) is one or more of ascorbic acid and tartaric acid, and more preferably ascorbic acid.
[0047] Preferably, the magnetic powder mentioned in step (3) is one or more of neodymium iron boron, samarium iron nitrogen, and samarium cobalt.
[0048] Preferably, in step (3), the magnetic powder and solution B are mechanically stirred in a water bath at 40°C until the reaction is complete, and then dried in a vacuum oven at 60°C.
[0049] The technical solution of the present invention will be further explained and described below with reference to several preferred embodiments, but the experimental conditions and setting parameters therein should not be regarded as limitations on the basic technical solution of the present invention. Furthermore, the scope of protection of the present invention is not limited to the following embodiments.
[0050] Example 1: Preparation of magnetic powder with superhydrophobic surface
[0051] (1) Add 0.05g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.005g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0052] (2) Add ascorbic acid to the solution obtained in step 1 until the pH of the solution is 5.8;
[0053] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0054] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0055] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0056] The test results are shown in Table 1.
[0057] Example 2: Preparation of magnetic powder with superhydrophobic surface
[0058] (1) Add 0.125g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0059] (2) Add ascorbic acid to the solution obtained in step 1 until the pH of the solution is 5.8;
[0060] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0061] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0062] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0063] The test results are shown in Table 1.
[0064] Comparative Example 1: Hydrophobic modification of magnetic powder using only benzimidazole compounds and organic acids.
[0065] This experiment is a comparative experiment of Example 1, and it is carried out according to the following steps:
[0066] (1) Add 0.125g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole to 50g of isopropanol and stir thoroughly until well mixed;
[0067] (2) Add ascorbic acid to the solution obtained in step 1 until the pH of the solution is 5.8;
[0068] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0069] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0070] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after immersing it in hot water at 90℃ for 20 days. The test results are shown in Table 1.
[0071] Comparative Example 2: Hydrophobic modification of magnetic powder using only organic acids and transition metal ions.
[0072] This experiment is a comparative experiment of Example 1, and it is carried out according to the following steps:
[0073] (1) Add 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0074] (2) Add ascorbic acid to the solution obtained in step 1 until the pH of the solution is 5.8;
[0075] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0076] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively. The test results are shown in Table 1.
[0077] Comparative Example 3: Hydrophobic modification of magnetic powder using only benzimidazole compounds and transition metal ions
[0078] This experiment is a comparative experiment of Example 1, and it is carried out according to the following steps:
[0079] (1) Add 0.125g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0080] (2) The solution obtained in step 1 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0081] The coercivity of the dried magnetic powder from step 2 and the dried magnetic powder from step 2 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0082] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0083] The test results are shown in Table 1.
[0084] Example 3: Preparation of magnetic powder with superhydrophobic surface
[0085] (1) Add 0.25g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.025g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0086] (2) Add ascorbic acid to the solution obtained in step 1 until the pH of the solution is 5.8;
[0087] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0088] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0089] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0090] The test results are shown in Table 1.
[0091] Example 4: Preparation of magnetic powder with superhydrophobic surface
[0092] (1) Add 0.125g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.0125g of zinc chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0093] (2) Add ascorbic acid to the solution obtained in the previous step until the pH of the solution is 5.8;
[0094] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0095] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0096] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0097] The test results are shown in Table 1.
[0098] Example 5: Preparation of magnetic powder with superhydrophobic surface
[0099] (1) Add 0.125g of 2-methylbenzimidazole and 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0100] (2) Add ascorbic acid to the solution obtained in the previous step until the pH of the solution is 5.8;
[0101] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0102] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0103] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0104] The test results are shown in Table 1.
[0105] Example 6: Preparation of magnetic powder with superhydrophobic surface
[0106] (1) Add 0.125g of 2-phenylbenzimidazole and 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0107] (2) Add ascorbic acid to the solution obtained in the previous step until the pH of the solution is 5.8;
[0108] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0109] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0110] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0111] The test results are shown in Table 1.
[0112] Example 7: Preparation of magnetic powder with superhydrophobic surface
[0113] (1) Add 0.125g of 2-[(2,4-dichlorophenyl)methyl]-1H-benzimidazole and 0.0125g of ferric chloride to 50g of isopropanol and stir thoroughly until well mixed;
[0114] (2) Add tartaric acid to the solution obtained in the previous step until the pH of the solution is 5.8;
[0115] (3) The solution obtained in step 2 is ultrasonically stirred and dispersed evenly. 50g of magnetic powder is added and mechanically stirred for 30min under a water bath at 40℃. The solution is then transferred to a vacuum oven at 60℃ for drying to obtain magnetic powder with a hydrophobic layer.
[0116] The coercivity of the dried magnetic powder from step 3 and the dried magnetic powder from step 3 after soaking in hot water at 90℃ for 24 hours were tested respectively.
[0117] The magnetic powder prepared in step (3) was mixed with PA12 resin at a mass ratio of 9:1 and then injection molded to obtain... The coercivity of the magnetic standard block was measured after it was soaked in hot water at 90℃ for 20 days.
[0118] The test results are shown in Table 1.
[0119] Table 1. Magnetic powder and its properties after soaking in hot water.
[0120]
[0121]
[0122] The above experimental results show that after the magnetic powder is treated according to the technical solution of the present invention, the water resistance is greatly improved, effectively protecting the coercivity index of the magnet. The composite magnet prepared using the magnetic powder has a significantly improved resistance to hot water corrosion and exhibits excellent water resistance.
Claims
1. A method for preparing magnetic powder with a superhydrophobic surface, characterized in that, Includes the following steps: Step (1): A certain mass of benzimidazole-based substances and salts containing transition metal ions are added to an organic solvent to obtain solution A; the mass ratio of the benzimidazole-based substances to the magnetic powder is 0.1%-0.5%:100%; Step (2): Add an organic acid to solution A and adjust the pH of the solution to 5.5-6.
5. Stir to disperse the solution evenly to obtain solution B; the organic acid is one of ascorbic acid and tartaric acid. Step (3): Magnetic powder is added to solution B in step (2), and after ultrasonic stirring, it is transferred to a vacuum oven and dried to obtain magnetic powder with a superhydrophobic surface. Benzimidazole is used as the main substance for forming the hydrophobic layer. After the surface treatment solution is prepared, it is mixed with the magnetic powder and reacts. During this process, imidazole molecules adsorb onto the surface of the magnetic powder by forming coordination bonds with the metal. Non-polar groups can also form a hydrophobic protective film on the surface of the magnetic powder.
2. The method according to claim 1, characterized in that, The benzimidazole substance mentioned in step (1) is one or more of alkylbenzimidazole and phenylbenzimidazole.
3. The method according to claim 2, characterized in that, The benzimidazole substance mentioned in step (1) is 2−[(2,4−dichlorophenyl)methyl]−1H−benzimidazole.
4. The method according to any one of claims 1-3, characterized in that, The mass ratio of the transition metal ion-containing salt to the benzimidazole substance in step (1) is 10%:100%.
5. The method according to any one of claims 1-3, characterized in that, In step (1), the transition metal ions in the salts containing transition metal ions are one or more of iron ions and zinc ions.
6. The method according to any one of claims 1-3, characterized in that, The salt containing transition metal ions mentioned in step (1) is ferric chloride.
7. The method according to claim 1, characterized in that, The magnetic powder mentioned in step (3) is one or more of neodymium iron boron, samarium iron nitrogen, and samarium cobalt.
8. A magnetic powder having a superhydrophobic surface, prepared by the method described in any one of claims 1-7.
9. A permanent magnet, characterized in that... The magnetic powder described in claim 8 is mixed with a resin matrix and then injection molded to obtain the product.
Citation Information
Patent Citations
Surface chemical treatment method of magnetic powder
CN108320899A
Rare-earth group magnetic powder and its surface treatment method
JP2001244106A
Surface treatment method for rare earth magnet powder
JP2004260036A